2003
DOI: 10.1021/es034005i
|View full text |Cite
|
Sign up to set email alerts
|

Nonylphenol Ethoxylates and Other Additives in Aircraft Deicers, Antiicers, and Waters Receiving Airport Runoff

Abstract: Samples of nine different formulations of aircraft deicer and antiicer fluids (ADAF) were screened for the presence of selected surfactants. Nonylphenol ethoxylates (NPnEO) were identified in three ADAF formulations, octylphenol ethoxylates were identified in two formulations, and six formulations contained alcohol ethoxylates. A preliminary field study was conducted at General Mitchell International Airport, Milwaukee, WI, to quantify NPnEO (n ) 1-15) and one of its byproducts, nonylphenol (NP), in airport ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
55
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 43 publications
4
55
0
1
Order By: Relevance
“…Finally, an inflow of 0.5-2.3 tons to Stockholm was estimated based on information of AP/APE in several other goods covering a large range of products, such as electronics, buildings and construction, the chemical industry, surface coatings (ECB 2002), water processing chemicals, perfumes and essences, antirust (Löfvén and Wahlberg 1997), de-icers (Corsi et al 2003) and several other applications (Products Register 2006).…”
Section: Amounts In Various Goodsmentioning
confidence: 99%
“…Finally, an inflow of 0.5-2.3 tons to Stockholm was estimated based on information of AP/APE in several other goods covering a large range of products, such as electronics, buildings and construction, the chemical industry, surface coatings (ECB 2002), water processing chemicals, perfumes and essences, antirust (Löfvén and Wahlberg 1997), de-icers (Corsi et al 2003) and several other applications (Products Register 2006).…”
Section: Amounts In Various Goodsmentioning
confidence: 99%
“…Wind drift during application and one of the most important criteria of ADAF that the fluids are readily removed from the surfaces of the aircraft during its takeoff are also resulting in a diffuse input into the ambient environment. In surface runoff of an airport the concentrations of 4Me-BT and 5Me-BT were 1,670 μg/L and 2,160 μg/L, respectively (Corsi et al 2003). 4-and 5Me-BT were also detected in snow and snowmelt runoff at an airport (Schaffner and Giger 2004).…”
mentioning
confidence: 98%
“…Thus, the rapid degradation of FO during melt water infiltration and high soil water saturation favors the development of anaerobic conditions, which might additionally decrease the degradation rate of PG . Previous studies found that ingredients of the ADF additive package exert a significant higher toxicity than PG and EG Cancilla et al 1998;Corsi et al 2003;Pillard 1995;Staples et al 2004). Adverse effects of the ADF additive package on biodegrading microorganisms may therefore additionally lower the degradation rate of the deicing chemicals in the soil.…”
Section: Introductionmentioning
confidence: 95%